Penerapan Model Problem Based Learning Untuk Meningkatkan Keterampilan Menyelesaikan Soal Cerita Pecahan - Mursolimah, Mursolimah (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
The purpose of this research is to improve improve story fraction problem solving skill among 4th grade students of SDN 3 Sembukan Sidoharjo Wonogiri in the academic year 2019/ 2020 by applying Problem Based Learning model. The research conducted was a Classroom Action Research (PTK). This research implemented in two cycles, each cycle consists of planning, acting, observing, and reflecting. The research result show that application of Problem Based Learning model can improve student’s story fraction problem solving skill. The average of story fraction problem solving skill in the pre-cycle 55.93; cycle I 74.79; and cycle II 84.38. While classical completeness in pra-cycle was 4 students (26.67%), cycle I was 12 students (80%), cycle II was 15 students (100%). The conclusion is application of Problem Based Learning model can improve story fraction problem solving skill among 4th grade students of SDN 3 Sembukan Sidoharjo Wonogiri in the academic year 2019/ 2020.